Mindful Self-Care and Resiliency (MSCR): protocol for a pilot trial of a brief mindfulness intervention to promote occupational resilience in rural general practitioners. Issue 6 (30th June 2018) - Rees, Clare; Craigie, Mark; Slatyer, Susan; Heritage, Brody; Harvey, Clare; Brough, Paula; Hegney, Desley
Abstract : Introduction: The Mindful Self-Care and Resiliency (MSCR) programme is a brief psychosocial intervention designed to promote resilience among various occupational groups. The intervention is based on the principles of mindfulness and also incorporates an educational self-care component. The current paper presents the protocol for a pilot study that will evaluate the effectiveness of this programme among general practitioners working in rural Queensland, Australia. Methods and analysis: We will measure the impact of the MSCR programme on levels of employee resilience (Connor-Davidson Resilience Scale; State-Trait Assessment of Resilience STARS), compassion satisfaction and compassion fatigue (Professional Quality of Life Scale), self-compassion (Self-Compassion Scale) and mood (Positive and Negative Affect Scale). We will also assess the impact of the programme on job satisfaction (The Abridged Job in General Scale), absenteeism/presenteeism (The WHO Health and Work Performance Questionnaire) and general well-being (WHO Five Well-being Index). Repeated measures analysis of variance will be used to analyse the impact of the intervention on the outcome measures taken at pre, post, 1-month, 3-month and 6-month follow-ups. We will conduct individual interviews with participants to gather data on the feasibility and acceptability of the programme. Finally, we will conduct an initial cost-effectiveness analysis of the programme. Ethics and dissemination: Approval for this study was obtained from the Curtin University Human Research ethics committee and the study has been registered with the Australian Clinical Trials Registry. Results will be published and presented at national and international congresses. Trial registration number: ACTRN12617001479392p; Pre-results.